2005
DOI: 10.4028/www.scientific.net/ssp.103-104.49
|View full text |Cite
|
Sign up to set email alerts
|

Organic Contamination Control in Silicon Surface Processing

Abstract: All rights reserved. No part of contents of this paper may be reproduced or transmitted in any form or by any means without the written permission of Trans Tech Publications Ltd, www.scientific.net.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The aforementioned standard cleaning protocol using isopropyl, acetone and DI water cannot remove the adsorbed volatile organic compounds from the surface (Cha et al 2017;Saga and Hattori 2005;Yan et al 2019a, b). It was likely that adsorbed organic compounds were present on the surface even prior to the visualization experiment.…”
Section: Dropwise Condensationmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned standard cleaning protocol using isopropyl, acetone and DI water cannot remove the adsorbed volatile organic compounds from the surface (Cha et al 2017;Saga and Hattori 2005;Yan et al 2019a, b). It was likely that adsorbed organic compounds were present on the surface even prior to the visualization experiment.…”
Section: Dropwise Condensationmentioning
confidence: 99%
“…Moreover, the preoccupied area that emerges after the coalescence is dry, i.e., it does not have the adsorbed water thin film. It has been reported that DI water cannot remove adsorbed organic compounds on the surface (Saga and Hattori 2005). This means that if an organic adsorbed film exists on the surface, it cannot be removed by the droplet.…”
Section: Dropwise Condensationmentioning
confidence: 99%
“…Supercritical carbon dioxide (SCCO 2 )-based technology has been proposed for various steps in device fabrication, such as wafer-surface cleaning, [42][43][44][45][46][47][48][49][50] drying of high-aspect ratio LSI structures, 29 developing of photoresists for EUV lithography, 51 and deposition of metals such as Cu and Ru. 52,53 SCCO 2 diffuses rapidly, has low viscosity and no surface tension, and thus, can penetrate easily into deep trenches and narrow vias of advanced LSI devices.…”
Section: Supercritical Fluid Cleaningmentioning
confidence: 99%
“…SCCO 2 -based processing has been investigated recently because of its potential to strip photoresists/ residues both in the front end of line (FEOL) and in the back end of line (BEOL) [43][44][45] and because it can restore the k-value of low-k materials for Cu low-k integration in the BEOL. 42 SCCO 2 applied to ultra-low-k porous material processing is a challengeable technique.…”
Section: Supercritical Fluid Cleaningmentioning
confidence: 99%
“…The adsorption of organic molecules at surfaces was traditionally related to the very large-scale integration (VLSI) process environment. 1,2 More recently, surface functionalization of transition-metal dichalcogenides (TMDs) such as molybdenum disulfide (MoS 2 ) has attracted interest due to their potential for novel nanoscale applications such as neuromorphic computing. [3][4][5][6][7][8][9] The fundamental basis of building a neuromorphic network involves emulating synaptic and neuronal behavior through nonlinear dynamical response of materials to external stimuli.…”
Section: Introductionmentioning
confidence: 99%